Transport, Logistics, and Economic Growth Nexus: A Cross-Country Analysis - Sabir Muhammad; Akram Muhammad; Mian Rehman Uddin (Transport and Telecommunication)
Transportation and logistics play a crucial role in the overall supply chain of a country by ensuring the timely delivery of goods for production and consumption. The current study investigates the relationship between economic growth and logistics performance across countries. The study’s significant contribution is using logistics performance data from a panel of 107 countries covering the period from 2007 to 2019 and applying panel data-based time-series econometric models to investigate the link between economic growth and logistics performance. The study confirms a long-term relationship between economic growth and logistics performance and shows that short-term disequilibrium is adjusted back to steady-state conditions. The findings suggest that policymakers should focus on developing all aspects of logistics performance rather than physical infrastructure.